Atypical squamous cells, cannot exclude high‐grade squamous intraepithelial lesion: Diagnostic features in surepath™ cervical samples. Issue 6 (16th July 2012) - Gupta, Nalini; Crossley, John; Dudding, Nick; Ellis, Kay; Smith, J. H. F.
Abstract This study was undertaken to identify the situations in which a diagnosis of "Atypical squamous cells, cannot exclude a high‐grade squamous intraepithelial lesion (ASC‐H)" is offered in SurePath™ cervical samples and to identify cytological criteria helpful in predicting high‐grade disease. 2, 335 (3.4%) SurePath samples reported as atypical squamous cells (ASC) over a period of 2 years, including 1, 112 cases with known hrHPV status were retrieved. 105/1, 112 cases were categorized into ASC‐H, and slides were available for review in 88/105 cases. These 88 samples were divided into two categories based on follow‐up histological outcome and hrHPV status–category A: cases with CIN2+ lesions on follow‐up (n = 48) and category B: cases with ≤CIN1 lesions or hrHPV negative status (n = 40). 78% (82/105) cases of ASC‐H tested positive for hrHPV. Overall CIN2+ lesions were found in 50.3% (53/105) cases. Of 88 cases reviewed, HCGs were noted in 56.3% (27/48) cases in category A and 75% (30/40) cases in category B. Dispersed metaplastic cells and scattered small atypical cells were seen in 37.5% (18/48) cases in category A and 12.5%(5/40) in category B. The majority of cases with dispersed atypical cells had <20 cells/sample and cases with HCGs had <10 HCGs per sample. The majority of the cases reported as ASC‐H contained HCGs. Of these groups with nuclear crowding, disorganization and those with steep edges ("blocks") are likely to predict high‐grade disease. The samples with only dispersed atypical cells had <20 cells/sample in majority of cases. In these, a disproportionate andespecially high nuclear: cytoplasmic ratio and irregular chromatin were the most useful features in predicting high‐grade disease. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.